2017
DOI: 10.1111/tct.12658
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of a peer-assisted mock PACES

Abstract: The mock PACES demonstrated benefits to confidence levels and knowledge both for tutees and tutors. The results demonstrate an effective model in examination preparation for PACES. This reinforces the holistic positive attributes gained from the use of PAL and mock examinations, whilst encouraging its use within the undergraduate syllabus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In a scoping review by Khan et al, peer assessors seem to benefit from improvement in feedback and teaching skills [9]. There are only few reported studies available on peer tutors who serve as assessors in a formative OSCE [2,4,9,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In a scoping review by Khan et al, peer assessors seem to benefit from improvement in feedback and teaching skills [9]. There are only few reported studies available on peer tutors who serve as assessors in a formative OSCE [2,4,9,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we could not find any studies that compared VPL to peer-assisted learning (PAL). In PAL, senior students provide their junior colleagues with teaching and learning support, which has the advantages that trainees often consider peer-trainers to be more approachable than faculty staff, and trainers are more familiar with courses because they have already passed them (Siddiqui et al, 2018). PAL is often used to teach clinical reasoning and practical skills in skills laboratories (Field et al, 2004), and it plays an integral part in so called student-run free clinics (Meah, Smith and Thomas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Roediger and Karpicke (2006) stated that testing can have direct and indirect effects on education. Improving information recall ability, is one of the direct benefits, also referred to as the 'testing effect' [4]. Examples of the indirect effect include more time directed to study and improvement in revision skills.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the indirect effect include more time directed to study and improvement in revision skills. Siddiqui et al (2017) investigated the effectiveness of a mock Practical Assessment of Clinical Examination Skills (PACES) to test fifth-year medical students [5]. They showed that their students felt significantly more confident after the mock, and 90.6% of students agreed that the mock PACES were more useful than a lecture-based format, bedside teaching or small group teaching to prepare for the examination.…”
Section: Introductionmentioning
confidence: 99%